Tracing Water Mass Mixing From the Equatorial to the North Pacific Ocean With Dissolved Neodymium Isotopes and Concentrations - Fuhr, Michael; Laukert, Georgi; Yu, Yang; Nürnberg, Dirk; Frank, Martin (Frontiers in Marine Science, 2021)
The sluggish water mass transport in the deeper North Pacific Ocean complicates the assessment of formation, spreading and mixing of intermediate and deep-water masses based on standard hydrographic parameters alone. Geochemical tracers sensitive to water mass provenance and mixing allow to better characterize the origin and fate of the prevailing water masses. Here, we present dissolved neodymium (Nd) isotope compositions (εNd) and concentrations ([Nd]) obtained along a longitudinal transect along ~180°E from ~7°S to ~50°N. The strongest contrast in Nd isotope signatures is observed in equatorial regions between surface waters (εNd ~0 at 4.5°N) and Lower Circumpolar Deep Water (LCDW) prevailing at 4500 m depth (εNd = -6.7 at 7.2°N). The Nd isotope compositions of equatorial surface and subsurface waters are strongly influenced by regional inputs from the volcanic rocks surrounding the Pacific, which facilitates the identification of the source regions of these waters and seasonal changes in their advection along the equator. Highly radiogenic weathering inputs from Papua-New-Guinea control the εNd signature of the equatorial surface waters and strongly alter the εNd signal of Antarctic Intermediate Water (AAIW) by sea water-particle interactions leading to an εNd shift from -5.3 to -1.7 and an increase in [Nd] from 8.5 to 11 pmol/kg between 7°S and 15°N. Further north in the open North Pacific, mixing calculations based on εNd, [Nd] and salinity suggest that this modification of the AAIW composition has a strong impact on intermediate water εNd signatures of the entire North Pacific allowing for improved identification of the formation regions and pathways of North Pacific Intermediate Water (NPIW). The deep-water Nd isotope signatures indicate a southern Pacific origin and subsequent changes along its trajectory resulting from a combination of water mass mixing, vertical processes and Nd release from seafloor sediments, which precludes their use as quantitative tracers of deep-water mass mixing. Moreover, comparison with previously reported data indicates that the Nd isotope signatures and concentrations below 100 m depth essentially remained stable over the past decades, which suggests constant impacts of water mass advection and mixing as well as of non-conservative vertical exchange and bottom release.